Knowledge Level of Rapeseed Mustard Growers of Sub-tropical and Temperate Region of Jammu and Kashmir State - Kumar, Rakesh; Slathia, P. S.; Peshin, Rajinder; Gupta, S.K.; Gupta, S.K. (Indian Journal of Extension Education, 2018)
The present research pursuit was undertaken to know the existing knowledge level of rapeseed mustard growers about different production and protection technologies of rapeseed mustard cultivation. The study was mainly conducted in subtropical and temperate region of Jammu division. The study revealed that from four districts 46.00 per cent of respondents had medium knowledge followed by 40.00 per cent respondents had low knowledge and only 14.00 per cent respondents had high knowledge respectively. The overall mean knowledge score was 9.98 (± 2.39). Majority of respondents (99.00%) had knowledge about insects and weeds of rapeseed mustard crop, (98.00%) of respondents had knowledge about thinning practice, (97.00%) and (81.00%) had knowledge of methods of weed control and time of thinning, (72.00%), (54.00%) and (53.00%) had knowledge of intercropping, quantity of urea and DAP fertilizer to be used in rapeseed mustard cultivation. Less percentage of respondents had knowledge about seed treatment, insecticides to be used against insects attacking rapeseed mustard crop. ANOVA results revealed that there was significant difference in knowledge level of mustard growers belonging to districts falling under sub-tropical zone as compared to temperate zone.
Keywords: Knowledge level; rapeseed mustard; production; protection; practices